A study on the stellar configurations in Almagest VII 1 - Recio, Gonzalo Luis (2022)
Book VII of the Almagest presents a list of stellar configurations –mostly stellar alignments– which have Hipparchus and Ptolemy as their authors. In this paper I will give a detailed study of these configurations. The analysis will be focused on the proper identification of the stars involved in them and the accuracy of the descriptions given in the text. Finally, I will provide a general comparative analysis of the alignments given by both astronomers.